TEACHING THE ―GLOBAL ECONOMY‖ TOPIC IN THE 7TH-GRADE GEOGRAPHY CLASS USING THE GAME METHOD - Avetisyan, G.; Grigoryan, L. (SUSh Scientific Proceedings, 2025)
Modern scientific and educational reforms are based on the formation and development of students' cognitive interests, their creative thinking, and ability to make independent decisions. Therefore, in order to ensure the comprehensive development of the student and organize training more effectively, great importance is attached to the use of interactive teaching methods. In the process of teaching geography in comprehensive schools, the need to use interactive methods, including game methods, is constantly increasing, and the importance and effectiveness of their use is considered as a means of educational innovation. The new textbook of ―Geography-7‖ /2023 edition/ includes a number of practical tasks, the organization of which will become much more educational, accessible and applicable using game methods. This allows you to turn geography from a theoretical and descriptive subject into an applied subject. In this article, the topic «Global Economy» was presented using the game method ―Domino of Knowledge‖, which was tested in the 7th grades of the Kamo secondary school of the Shirak marz and the Gyumri Academic College. The use of this game method among students increases the effectiveness of mastering the subject ―Geography‖, forms many personal qualities (fairness, persistence, quick orientation, ability to predict), as well as the ability to cooperate and cognitive independence.